Non-Linear Effects and The Moderating Role of Cash Flow Slack: Financial Management Perspective - Mamay Komarudin; Tabroni (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study aims to examine the effectiveness of marketing investment in improving firm performance by identifying whether a specific threshold of financial slack influences the relationship between marketing intensity and sales outcomes in Indonesian food and beverage companies. The study is motivated by the ongoing debate in the literature regarding whether marketing investment consistently improves firm performance or whether its effectiveness depends on internal financial conditions. To address this issue, the research investigates whether the availability of financial slack, measured through firms’ cash position, alters the impact of marketing investment on sales performance and profitability. Methods - The study employs a quantitative research design using panel data from seven food and beverage companies listed on the Indonesia Stock Exchange during the period 2019–2024, resulting in 42 firm–year observations. The analysis applies Hansen’s panel threshold regression model to identify non-linear effects and employs a sequential causality model estimated through pooled ordinary least squares to examine the causal pathway linking cash position, marketing intensity, sales intensity, and profitability. Findings - The findings reveal a statistically significant threshold at a cash position of 18.73%, indicating that the effectiveness of marketing investment differs across financial regimes. In the low-cash regime, marketing intensity shows a stronger influence on sales intensity (β = 1.2475), while in the high-cash regime the effect decreases (β = 0.1398). The sequential analysis further demonstrates that financial slack positively influences sales intensity (β = 5.756, p < 0.01), which subsequently contributes to firm profitability (β = 0.061, p < 0.01). Research Implication - These results indicate that financial slack acts as a strategic enabler that supports the effectiveness of marketing investment in generating firm performance. However, the relatively small sample size and sector-specific focus limit the generalizability of the findings to other industries. Originality - The study contributes to the literature by integrating organizational slack theory and the resource-based view to explain non-linear relationships between financial resources and marketing effectiveness and by applying panel threshold regression to marketing finance research in an emerging market context.